Comparações teóricas e práticas sobre geometrias de mancais magnéticos - Pinto, Paulo Henrique Silva (2018)
Active Magnetic Bearings are mechatronic systems that generate forces through controlled magnetic fields, used to keep rotors centered. These bearings can be used in technological applications that require high speeds, absence of lubrication, longer service life, greater vacuum, lower maintenance costs, lower temperatures and higher purity environments. This work presents a theoretical and practical comparison between the conventional structure that has eight poles operating in a way that the magnetic flux crosses simultaneously two adjacent poles, with a new structure that has four poles generating interconnected magnetic fluxes. The theoretical results provide for greater equivalent mechanical rigidity for this new structure, compared to conventional active magnetic bearings. The development of a mathematical model that allows these predictions, the use of recently constructed prototypes to test if expectations are true and the implementation of current and position control system in a DSP are the main objectives of this work.